2010
DOI: 10.3109/13625187.2010.532999
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of contraceptive methods: A review of the literature

Abstract: Our review broadly confirms the hierarchy of contraceptive effectiveness in descending order as: (1) female sterilisation, long-acting hormonal contraceptives (LNG-IUS and implants); (2) Cu-IUDs with ≥ 300 mm2 surface area; (3) Cu-IUDs with < 300 mm2 surface area and short-acting hormonal contraceptives ( injectables, oral contraceptives, the patch and vaginal rings), (4) barrier methods and natural methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 0 publications
0
54
0
6
Order By: Relevance
“…It is worth noting that the "very effective" methods are distinguished from other major methods by a substantially reduced risk of unintended pregnancy but also by coital independence -meaning they do not require a specific intervention at the time of intercourse. Although estimates of efficacy associated with individual contraceptive methods vary across countries and across individual studies, our broader classification of efficacy applies broadly (Mansour, Inki, and Gemzell-Danielsson 2010;Moreau et al 2007;Trussell 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that the "very effective" methods are distinguished from other major methods by a substantially reduced risk of unintended pregnancy but also by coital independence -meaning they do not require a specific intervention at the time of intercourse. Although estimates of efficacy associated with individual contraceptive methods vary across countries and across individual studies, our broader classification of efficacy applies broadly (Mansour, Inki, and Gemzell-Danielsson 2010;Moreau et al 2007;Trussell 2011).…”
Section: Methodsmentioning
confidence: 99%
“…1 The withdrawal method has a high failure rate and leads to around 50% of unsafe abortions. 2 On the other hand, although IUD is an effective contraceptive method, pregnancy due to failure of this method has its adverse effects; the failure rate of Cu-IUDs is 0.8% (0.1-1.4 per 100) 3,4 and in Iran, pregnancy with this method is 1 continued unless the mother is at risk. The IUD is removed in case of visibility of its tail.…”
Section: Introductionmentioning
confidence: 99%
“…1 Subsequently it has been found that formulations with ethinyloestradiol 20 microgram are likely to be as effective as the 30-35 microgram pills while possibly reducing the oestrogenic effects such as nausea, bloating and breast tenderness. 2 However, there may be an increase in unscheduled bleeding.…”
Section: Introductionmentioning
confidence: 99%